Expansão urbana em Divinópolis-MG: ideias, práticas e agentes - Érick Aparecido de Lacerda (2022)
This research investigates the process of urban expansion in Divinópolis, a non-metropolitan medium city in the State of Minas Gerais. The analysis starts from the initial occupation of Divinópolis until its recent developments to observe, through the historical perspective, the changes, permanence, and specificities in the urbanization of the municipality. We sought to relate what is thought and done in the territory by articulating the morphology of the urban fabric, the roles carried out by the different agents, and the control and planning policy undertaken by the public administration. To this end, we crosschecked primary sources, statistical data, theoretical references, interviews, and maps as a form to characterize the plurality of ideas, practices, and agents in the production of the urban space of the municipality. The research demonstrates the transformations of the initial compact urban form to a dispersed one, the advances and limits of the proposed public policies, the formation of the land market, the role of urban and regional planning, and the contradictions caused in space.